Enhanced Heat Transfer of a Heat Exchanger Tube Installed with V-Shaped Delta-Wing Baffle Turbulators - Samruaisin, Prachya; Maza, Rangsan; Thianpong, Chinaruk; Chuwattanakul, Varesa; Maruyama, Naoki; Hirota, Masafumi; Eiamsa-ard, Smith (My University, 2023)
The influences of V-shaped delta-wing baffles on the thermohydraulic performance characteristics in a round tube were experimentally tested. The V-shaped delta-wing baffles having a set number of wings (N = 4, 6, and 8) were comparatively tested. The V-shaped delta-wing baffles with various pitch ratios of P/D = 2.0, 2.5, and 3.0 were thoroughly fitted inside a tube. In the present work, the baffles were responsible for both the recirculation/reverse flow behind the solid baffle and the longitudinal vortex flow behind the V-shaped wing. The V-shaped winged baffles with N = 8 produced high heat transfer rates by promoting the development of reverse and vortex flows. These currents aid in fluid mixing between the two streams. Experimental results suggested that utilizing V-shaped delta-wing baffles having N = 4, 6, and 8 led to Nusselt number enhancement of up to 97–105.6%, 105.8–127.8% and 114.8–138.9%, respectively. When N was 8, the V-shaped wings baffles created additional multi vortex flows, which resulted in some fluid mixing between the vortex and the reverse flow. It was discovered that a greater turbulent intensity is imparted to the flow that was occurring between the V-shaped delta-wing baffles, which led to an increase in the rate of heat transfer when the pitch ratio was decreased. The increase in Nusselt number was up to 118.26–151.3% more than it was in a tube with the lowest pitch ratio (P/D = 2.0). It was also found that the baffles with N = 8 wings and P/D = 3.0 offered a maximum aerothermal performance factor (APF) of 1.01. Furthermore, the V-shaped delta-wing baffles have the potential for energy savings at low Re ≤ 6000, indicated by the APF beyond unity.
Keywords: aerothermal performance; heat transfer; turbulator; V-shaped winged-baffle